Pelatihan Pengembangan Media Pembelajaran Berbasis Teknologi Informasi Bagi Guru-guru SMP - Alicia A.E. Sinsuw; Alwin M. Sambul (Jurnal Teknik Elektro dan Komputer, 2017)
Abstract – IbM activities for junior high school teachers through training the development of information technology-based learning media is an activitiy service-oriented society in the field of education. Learning activities which are still conventional in nature will have an impact on students’ boredom so will experience difficulties in understanding the basic concepts. As identified, problems found is the lack of ability of teachers in mastery of technology results in lack of teachres’ creativity in preparation of design learning in rder to support the teaching and learning activities.The training of information technology-based learning media development helps teachers in preparing the attractive and up-to-date learning materials for students by using the facilities and access to information technology.The stages of activities implementation conducted in the form of training for teachers in deigning teaching material by using various applications, such as, the making of slides by using power point and video applications, and also, by using gadget as learning media and grade management.The next stage is the teacher/trainee mentoring in designing the appropriate learning media according to the training given.Key words : learning media, information technology, gadget, school, junior high schoolRingkasan— Kegiatan IbM guru-guru SMP melalui pelatihan pengembangan media pembelajaran berbasis teknologi informasi merupakan kegiatan Pengabdian pada Masyarakat yang berorientasi pada bidang pendidikan. Kegiatan pembelajaran yang masih bersifat konvensional akan berdampak pada kebosanan siswa sehingga mengakibatkan kesulitan dalam memahami konsep dasar. Permasalahan yang ditemukan adalah kurangnya kemampuan guru dalam penguasaan teknologi mengakibatkan kurang kreatifnya penyusunan rancangan pembelajaran dalam menunjang kegiatan belajar mengajar. Pelatihan pengembangan media pembelajaran berbasis teknologi informasi membantu guru dalam mempersiapkan materi belajar yang menarik dan up to date bagi siswa menggunakan fasilitas dan akses teknologi informasi. Tahapan pelaksanaan kegiatan yang dilakukan berupa pelatihan bagi para guru dalam merancang materi ajar dengan menggunakan berbagai aplikasi antara lain pembuatan slide menggunakan power point dan video, pemanfaatan gadget sebagai media belajar serta pengelolaan nilai. Tahapan selanjutnya adalahpendampingan guru/peserta pelatihan dalam mendesain perangkat-perangkat pembelajaran sesuai pelatihan yang diberikan.Kata kunci : Media pembelajaran, teknologi informasi, gadget, sekolah, SMP